The Effects of English Proficiency among Childhood Immigrants: Are Hispanics Different? - Mevlude Akbulut-Yuksel; Hoyt Bleakley; Aimee Chin (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
We test whether the effect of English proficiency differs between Hispanic and non-Hispanic immigrants. Using 2000 U.S. Census microdata on immigrants who arrived before age 15, we relate labor market, education, marriage, fertility and location of residence variables to their age at arrival in the U.S., and in particular whether that age fell within the "critical period" of language acquisition. We interpret the observed difference in outcomes between childhood immigrants who arrive during the critical period and those who arrive later (adjusted for non-language-related age-at-arrival effects using childhood immigrants from English-speaking countries) as an effect of English- language skills and construct an instrumental variable for English-language skills. We find that both Hispanics and nonHispanics exhibit lower English proficiency if they arrive after the critical period, but this drop in English proficiency is larger for Hispanics. The effect of English proficiency on earnings and education is nevertheless quite similar across groups, while some differences are seen for marriage, fertility, and location of residence outcomes. In particular, although higher English proficiency reduces (for both groups) the number of children and the propensity to be married, marry someone with the same birthplace or origin, and live in an "ethnic enclave," these effects are smaller for Hispanics.
Keywords: 330